A novel silicon interposer based high security integration approach for microsystem. (May 2021) - Zhu, Chunsheng; Guo, Pengfei; Zhang, Lichao; Yan, Yingjian
Abstract: Security problems of microsystem have gained widespread attention for its applications in many fields. However, current integration technologies cannot provide a security solution against physical invasive attack and side channel attack effectively. In this paper, a novel silicon interposer structure with embedded trenches was proposed to achieve high security microsystem integration. Chips were embedded in the trenches with metal shielding wires protected in all directions, which formed a Faraday cage. Experiment indicated that the Faraday cage could shield the electromagnetic radiation of the chips dramatically and the electromagnetic based side channel attack could be mitigated. Besides, metal shielding wires also formed a loop. Physical invasive attack on the chips would unavoidably damage the loop and could be detected. Since fine pitch random Hamiltonian metal wires could be fabricated on the silicon interposer, the designed structure had a high detection resolution.